2011
DOI: 10.1111/j.1447-0594.2011.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive behavior in patients with dementia: Correlates and management

Abstract: Over the course of the illness AB occurs in 30 to 50% of patients and causes extreme stress for caregivers. Careful identification of target symptoms and their consequences, non-pharmacological approaches, and use of the least harmful medication for the shortest period of time should be the guiding principle of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 55 publications
1
47
0
1
Order By: Relevance
“…Dementia patients with frontal predominance often react impulsively to tempting environmental situations involving sexual or other objects of interest, without concern for the consequences; in addition, the commonest sociopathic acts in dementia are physical assaults that are sometimes correlated with misperceptions and sometimes with frank delusions . Several studies have reported increased AB in persons suffering from dementia compared with the normal population . AB in dementia might start when, with increasing cognitive impairment, people misinterpret the environment; for example, perceiving intimate care as a threat .…”
Section: Resultsmentioning
confidence: 99%
“…Dementia patients with frontal predominance often react impulsively to tempting environmental situations involving sexual or other objects of interest, without concern for the consequences; in addition, the commonest sociopathic acts in dementia are physical assaults that are sometimes correlated with misperceptions and sometimes with frank delusions . Several studies have reported increased AB in persons suffering from dementia compared with the normal population . AB in dementia might start when, with increasing cognitive impairment, people misinterpret the environment; for example, perceiving intimate care as a threat .…”
Section: Resultsmentioning
confidence: 99%
“…The development and implementation of strategies to help caregivers administrate medications to their patients may indeed reduce the strain related to such tasks and increase their level of satisfaction with the care delivered. A reduced level of caregiver burden and distress has also been associated with a decreased risk of developing behavioral symptoms in AD patients and with an overall improved quality of life for their families [6,28,29]. Such positive effects result in a more prolonged in-home care provision for patients, with an overall reduction of costs of institutionalization [10,30].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that 30–50% of behavioral disturbances in dementia are severe aggression (Cipriani, Vedovello, Nuti, & Di Fiorino, 2011; Kunik et al, 2010), demonstrating the importance of proficiency in assessing the development and triggers for aggressive behavior. As a result of the many different medical, social, and emotional factors that may play a part in behavior, providers must develop sensitivity to the many aspects of the patient’s life and become comfortable either assessing complex patterns of behavior or making referrals to allied professionals who can assist with this process.…”
Section: Assessing and Intervening: Aggression In Dementiamentioning
confidence: 99%